2014
DOI: 10.3762/bjoc.10.38
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow nitration in miniaturized devices

Abstract: SummaryThis review highlights the state of the art in the field of continuous flow nitration with miniaturized devices. Although nitration has been one of the oldest and most important unit reactions, the advent of miniaturized devices has paved the way for new opportunities to reconsider the conventional approach for exothermic and selectivity sensitive nitration reactions. Four different approaches to flow nitration with microreactors are presented herein and discussed in view of their advantages, limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
78
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 39 publications
0
78
0
4
Order By: Relevance
“…Levy and coworkers described the nitration of benzene using a small scale stirred-tank reactor [14]. It is not, however, until the beginning of the 21st century when miniaturized reactors (microreactors) have been perceived to have made their entry into the development of continuous-flow arene nitrations [6], with important contributions to the field from the groups of Loebbecke [15] or Roberge [7, 16], among others.Within this context, we believe that the pioneering research by Brennecke and Kobe [17] has received too little or no attention in the recent flow literature. In 1956, these authors reported the mixed acid nitration of toluene in a miniature continuous-flow reactor from which useful kinetic data could be obtained for this very fast transformation.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Levy and coworkers described the nitration of benzene using a small scale stirred-tank reactor [14]. It is not, however, until the beginning of the 21st century when miniaturized reactors (microreactors) have been perceived to have made their entry into the development of continuous-flow arene nitrations [6], with important contributions to the field from the groups of Loebbecke [15] or Roberge [7, 16], among others.Within this context, we believe that the pioneering research by Brennecke and Kobe [17] has received too little or no attention in the recent flow literature. In 1956, these authors reported the mixed acid nitration of toluene in a miniature continuous-flow reactor from which useful kinetic data could be obtained for this very fast transformation.…”
mentioning
confidence: 99%
“…Levy and coworkers described the nitration of benzene using a small scale stirred-tank reactor [14]. It is not, however, until the beginning of the 21st century when miniaturized reactors (microreactors) have been perceived to have made their entry into the development of continuous-flow arene nitrations [6], with important contributions to the field from the groups of Loebbecke [15] or Roberge [7, 16], among others.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Invited presentations discussed (1) photochemical transformations by T. Noël [4], S. Fuse [5], M. Oelgemöller [6], and A. Beeler [7]; (2) generation and safe usage of hazardous species by K. Hirose [8], C. O. Kappe [9,10], and T. Wirth [11]; (3) carbonylation reactions by I. Ryu [12]; (4) catalysis by N. Kumagai [13] and R. Souza [14]; (5) multistep synthetic transformations by T. Jamison [15,16] and A. Kulkarni [17]; (6) polymer construction by C. Serra [18]; and finally, (7) general advances in flow chemistry by M. Organ [19], D. Kim [20,21], and E. Kumacheva [22]. The popularity of these transformations is driven by the need to overcome the limitations of conventional batch reactions such as mixing, thermal control, safety metrics, and scale-up issues.…”
mentioning
confidence: 99%